Coamplification of Mycobacterium leprae genome sections by real-time PCR: Detection of the pathogen and the possibility of a semi-quantitative assessment of the bacterial load - D. A. Verbenko; A. E. Karamova; V. S. Solomka; A. A. Kubanov; D. G. Deryabin (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Aim. To develop a method for coamplification of single-copy genes and repetitive elements of the Mycobacterium leprae genome in the analysis of clinical material from leprosy patients with an assessment of the clinical significance of the study results.Materials and methods. Skin scarification and biopsy samples from patient R. with a diagnosis of "A30.5 Leprosy. Multibacillary form. Lepromatous type. Active stage" were used as empirical material for the study. A search for M. leprae DNA in the clinical material was performed by the method of real-time PCR (RT-PCR) using primers and hydrolysis probes for the single-copy species-specific genes rpoB (encodes the β-subunit of bacterial RNA polymerase), sodA (encodes the superoxide dismutase enzyme) and mntH (encodes the manganese transport protein), as well as for RLEP - the non-coding repetitive element of the genome.Results. Using various RT-PCR assays, consistent results were obtained concerning the presence or absence of M. leprae DNA in the studied clinical samples. The high sensitivity of PCR was confirmed for the detection of the repetitive element RLEP compared to the single-copy genes rpoB, sodA and mntH, which consists in reducing the number of amplification cycles (Ct) needed for exceeding the threshold fluorescence value of hydrolysis probes and leading to the maximum intensity of the fluorescence signal. When constructing standard graphs for calibrating the accumulation of a fluorescent signal for simultaneously analyzed portions of the M. leprae genome in dilutions from 1 to 1,000, significant differences in the results of co-amplification were noted depending on the quantitative presence of the DNA being detected.Conclusion. Coamplification of M. leprae genome sections with varying degrees of copy number variation by the RTPCR method provides for effective detection of the M. leprae DNA in clinical material and forms a basis for a quantitative assessment of the bacterial load in skin scarification and biopsy samples.